Importin-Mediated Pathological Tau Nuclear Translocation Causes Disruption of the Nuclear Lamina, TDP-43 Mislocalization and Cell Death - Candia, Robert F.; Cohen, Leah S.; Morozova, Viktoriya; Corbo, Christopher; Alonso, Alejandra D. (Frontiers in Molecular Neuroscience, 2022)
Tau is a cytosolic protein that has also been observed in the nucleus, where it has multiple proposed functions that are regulated by phosphorylation. However, the mechanism underlying the nuclear import of tau is unclear, as is the contribution of nuclear tau to the pathology of tauopathies. We have previously generated a pathological form of tau, PH-tau (pseudophosphorylated at S199, T212, T231, and S262) that mimics AD pathological behavior in cells, Drosophila, and a mouse model. Here, we demonstrated that PH-tau translocates into the nucleus of transiently transfected HEK-293 cells, but wildtype tau does not. We identified a putative importin binding site in the tau sequence and showed that disruption of this site prevents tau from entering the nucleus. We further showed that this nuclear translocation is prevented by inhibitors of both importin-α and importin-β. In addition, the expression of PH-tau resulted in an enlarged population of dying cells, which is prevented by blocking its entry into the nucleus. PH-tau-expressing cells also exhibited disruption of the nuclear lamina and mislocalization of TDP-43 to the cytoplasm. We found that PH-tau does not bundle microtubules, and this effect is independent of nuclear translocation. These results demonstrate that tau translocates into the nucleus through the importin-α/β pathway and that PH-tau exhibits toxicity after its nuclear translocation. We propose a model where hyperphosphorylated tau not only disrupts the microtubule network, but also translocates into the nucleus and interferes with cellular functions, such as nucleocytoplasmic transport, inducing mislocalization of proteins like TDP-43 and, ultimately, cell death.